Evaluating a polymicrobial biofilm model for structural components by co-culturing Komagataeibacter hansenii produced bacterial cellulose with Pseudomonas aeruginosa PAO1 - Mahadevaswamy, Usha Rani (2024)
A polymicrobial biofilm model of Komagataeibacter hansenii and Pseudomonas 7 aeruginosa was developed to understand whether a pre-existing matrix affects the 8 ability of another species to build a biofilm. P. aeruginosa was inoculated onto the 9 preformed K. hansenii biofilm consisting of a cellulose matrix. P. aeruginosa PAO1 10 colonized and infiltrated the K. hansenii bacterial cellulose biofilm (BC), as indicated 11 by the observation of cells at 19 µm depth in the translucent hydrogel matrix. Bacterial 12 cell density increased with biofilm depth up to the imaging limit (17 µm). On day 5 the 13 average bacterial count across sections was 67+4% P. aeruginosa PAO1 and 33+6% 14 K. hansenii. Biophysical characterization of the biofilm indicated that colonization by 15 P. aeruginosa modified the biophysical properties of the matrix, in terms of increased 16 density, heterogeneity, degradation temperature and thermal stability, and reduced 17 crystallinity, swelling ability and moisture content. This further indicates colonization of 18 the biofilm by P. aeruginosa. Nonetheless, while eDNA fibres were present on the 19 surface of co-cultured biofilm on Day 1, their abundance decreased over time, and by 20 day 5, no eDNA was observed, either on the surface or within the matrix. Additionally, 21 P. aeruginosa colonization without its key viscoelastic component did not change the 22 mechanical properties of the biofilm. This demonstrates that a pre-existing biofilm 23 scaffold of K. hansenii inhibits aeruginosa PAO1 eDNA production, suggesting that 24 eDNA production is a response by P. aeruginosa to the viscoelastic properties of its 25 environment.